2012
DOI: 10.3892/ijo.2012.1688
|View full text |Cite
|
Sign up to set email alerts
|

The microtubule targeting agent PBOX-15 inhibits integrin-mediated cell adhesion and induces apoptosis in acute lymphoblastic leukaemia cells

Abstract: Abstract. Although recent decades have seen an improved cure rate for newly diagnosed paediatric acute lymphoplastic leukaemia (ALL), the treatment options for adult ALL, T-cell ALL (T-ALL) and relapsed disease remain poor. We have developed a novel series of pyrrolo-1,5-benzoxazepine (PBOX) compounds and established their anticancer efficacy in a variety of human tumour cell types. Here, we demonstrate that PBOX-15 inhibits cell growth, and induces G2/M cell cycle arrest and apoptosis in both T-ALL and B-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…When utilized as anticancer agents, MTAs generally cause cell cycle arrest and apoptosis, as a consequence of caspase activation through the intrinsic apoptotic pathway. Similar effects have been observed in leukemia cells; certain MTAs, including PBOX-15 (4), CA4P (5) and PBOX-6 (6), displayed cytotoxic efficiency in various leukemia cell types through the inhibition of cellular proliferation. In addition, it has been demonstrated that CA4P, a novel tubulin-destabilizing agent, reduced the interaction of leukemia cells with neovessels by downregulating the expression of the adhesion molecule VCAM-1, thereby increasing leukemia cell death (5).…”
Section: Introductionsupporting
confidence: 65%
“…When utilized as anticancer agents, MTAs generally cause cell cycle arrest and apoptosis, as a consequence of caspase activation through the intrinsic apoptotic pathway. Similar effects have been observed in leukemia cells; certain MTAs, including PBOX-15 (4), CA4P (5) and PBOX-6 (6), displayed cytotoxic efficiency in various leukemia cell types through the inhibition of cellular proliferation. In addition, it has been demonstrated that CA4P, a novel tubulin-destabilizing agent, reduced the interaction of leukemia cells with neovessels by downregulating the expression of the adhesion molecule VCAM-1, thereby increasing leukemia cell death (5).…”
Section: Introductionsupporting
confidence: 65%
“…19,30,31 Therefore, it seemed interesting to assess whether, at doses lower than those used in the assessment of cell proliferation, PBOX-15 is able to improve the sensitivity to treatment with oxaliplatin or with 5-FU. Oxaliplatin in combination with 5-Fluorouracil and leucovorin (FOLFOX) has been approved for metastatic CRC therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The non-apoptotic subset of the PBOXs (PBOX-1,-2,-21) exert their anti-proliferative effects by inducing a G1 cell cycle arrest 2, 8, 9. On the other hand, the pro-apoptotic subset of PBOXs (PBOX-6, -15, -16) induce a G2 / M arrest subsequent to apoptosis 6, 13-15, 19-22, 24, 29. In each case, the aforementioned cell cycle arrest induced by a representative member of each group was confirmed using several biochemical techniques.…”
Section: Modulators Of the Cell Cyclementioning
confidence: 99%
“…Apart from targeting tubulin in mitotic cells, the tubulin targeting properties of the PBOXs can also impede other functions involved in tumour progression such as cell adhesion, spreading, migration and angiogenesis 19, 22, 36. Tumour neovascularisation occurs by non-sprouting and sprouting angiogenesis, although the latter is more prominent 59.…”
Section: Other Anticancer Propertiesmentioning
confidence: 99%
See 1 more Smart Citation